Formation and Stability of Lipid Membrane Nanotubes - Bahrami, Amir Houshang; Hummer, Gerhard (ACS nano, 2017)
Lipid membrane nanotubes are abundant in living cells, even though tubules are energetically less stable than sheet-like structures. According to membrane elastic theory, the tubular endoplasmic reticulum (ER), with its high area-to-volume ratio, appears to be particularly unstable. We explore how tubular membrane structures can nevertheless be induced and why they persist. In Monte Carlo simulations of a fluid–elastic membrane model subject to thermal fluctuations and without constraints on symmetry, we find that a steady increase in the area-to-volume ratio readily induces tubular structures. In simulations mimicking the ER wrapped around the cell nucleus, tubules emerge naturally as the membrane area increases. Once formed, a high energy barrier separates tubules from the thermodynamically favored sheet-like membrane structures. Remarkably, this barrier persists even at large area-to-volume ratios, protecting tubules against shape transformations despite enormous driving forces toward sheet-like structures. Molecular dynamics simulations of a molecular membrane model confirm the metastability of tubular structures. Volume reduction by osmotic regulation and membrane area growth by lipid production and by fusion of small vesicles emerge as powerful factors in the induction and stabilization of tubular membrane structures.